Retracted: Increased resting‐state activity in the cerebellum with mothers having less adaptive sensory processing and trait anxiety. Issue 15 (16th July 2021) - Sakakibara, Nobuko; Makita, Kai; Hiraoka, Daiki; Kasaba, Ryoko; Kuboshita, Ryo; Shimada, Koji; Fujisawa, Takashi X.; Tomoda, Akemi
Abstract: Child‐rearing mothers with high levels of trait anxiety have a tendency for less adaptive sensory processing, which causes parenting stress. However, the neural mechanisms underlying this sensory processing and trait anxiety remain unclear. We aimed to determine the whole‐brain spontaneous neural activity and sensory processing characteristics in mothers with varying parenting stress levels. Using resting‐state functional magnetic resonance imaging, we assessed mothers caring for more than one preschool aged (2–5 years) child and presenting with varying levels of sensory processing, trait anxiety, and parenting stress. Spontaneous neural activities in select brain regions were evaluated by whole‐brain correlation analyses based on the fractional amplitude of low‐frequency fluctuations (fALFF). We found significant positive correlations between levels of sensory processing with trait anxiety and parenting stress. Mothers having less adaptive sensory processing had significantly increased resting‐state network activities in the left lobule VI of the cerebellum. Increased fALFF values in the left lobule VI confirmed the mediation effect on the relationship between trait anxiety and sensory processing. A tendency for less adaptive sensory processing involving increased brain activity in lobule VI could be an indicator of maternal trait anxiety and the risk of parenting stress. Abstract : Mothers having less adaptive sensory processing had significantly increased resting‐state network activities in the left lobule VI of the cerebellum. Increased the fractional amplitude of low‐frequency fluctuations (fALFF) values in the left lobule VI confirmed the mediation effect on the relationship between trait anxiety and sensory processing. A tendency for less adaptive sensory processing involving increased brain activity in lobule VI could be an indicator of maternal trait anxiety and the risk of parenting stress.